Gestión Administrativa en el mercado 4 de Mayo de la ciudad de Babahoyo. - Mosquera Murillo, Jefferson Bolivar (2018)
In Ecuador, the supply centers are institutions, organized and run by the municipalities of the city where they are established, the process of the trade in our country consists of three levels referring to the development that consists of taking the products to the final consumer, the first degree includes the exchange between wholesale centers and distributors; the second degree between the wholesale distributor and the retailers; the third degree among retailers and final consumers. The city of Babahoyo has four food centers, where they are offered various products, these establishments are strategically distributed in the locality, carrying out its activities. The Supply Center, May 4, is located in the sector known as PJ, where you can see a number without disadvantages with respect to administrative management, which has not been implemented as should be applied, directly affecting the members of the establishment